Bioremediation of dairy wastewater using bacteria: a panoramic review (Research, Society and Development, 2022)
The Bioremediation consists of applying microorganisms to reduce, eliminate or transform organic or inorganic polluting compounds into inert substances. Solid and liquid wastes are generated daily in industrial activities and, among the food processing industries, the dairy sector presents a large number of liquid effluents due to its extensive use of water in various activities and sectors. For an efficient treatment of effluents, it is essential to understand the microbiota of the wastewater, its biochemical characteristics and metabolic activity, as well as the origin of the polluting compounds. The growing demand for products derived from livestock and agricultural activity drives the search for environmental technologies capable of providing sustainable development. In this scenario, biotechnological studies and bioremediation applications are increasingly gaining ground both for environmental control and for application in value-added products. The purpose of this review is to present and discuss the most recent and used technologies for bioremediation of effluents from dairy industries using bacteria.